2012
DOI: 10.2478/v10045-012-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of weed regulation methods in spring wheat cultivated in integrated, conventional and organic crop production systems

Abstract: Abstract:The research was conducted from 2008 to 2010, and compared the influence of different weed control methods used in spring wheat on the structure of the weed communities and the crop yield. The study was carried out at the Experimental Station of the Institute of Soil Science and Plant Cultivation -State Research Institute in Osiny as part of a long-term trial where these crop production systems had been compared since 1994. In the conventional and integrated systems, spring wheat was grown in a pure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The results show high efficacy of weed control in spring wheat in the organic system by the interaction of 5-year crop rotation, successful undersown clover with grasses and dense canopy of wheat with large ability to compete with weeds. The effectiveness of mixed crops of cereals with legumes in reducing weed confirms the results of other authors [36,37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results show high efficacy of weed control in spring wheat in the organic system by the interaction of 5-year crop rotation, successful undersown clover with grasses and dense canopy of wheat with large ability to compete with weeds. The effectiveness of mixed crops of cereals with legumes in reducing weed confirms the results of other authors [36,37].…”
Section: Discussionsupporting
confidence: 90%
“…In the organic system weed infestation in cereals is generally greater than in the more intensive crop production systems where herbicides are used [34,35]. However, the application of agricultural practices according to Good Agricultural Practices, proper crop rotation, delaying sowing time, increasing the amount of seed, maintaining good soil structure, with a high content of organic matter allows to keep the weeds at a level not causing a significant yield decrease [22,36]. The results show high efficacy of weed control in spring wheat in the organic system by the interaction of 5-year crop rotation, successful undersown clover with grasses and dense canopy of wheat with large ability to compete with weeds.…”
Section: Discussionmentioning
confidence: 99%
“…The studied wheat species did not show greater susceptibility to weed infestation than is observed in the spring common wheat grown under comparable conditions. In the study by Bhaskar et al [65], weed mass in spring wheat grown without the use of herbicides was 52% lower, while in the study by Feledyn-Szewczyk [66], the number of weeds in spring wheat was about 70% larger than that found in Persian and Indian dwarf wheat. The present study did not confirm the effect of sowing density on weed infestation of wheat found by Haliniarz and Kapeluszny [23].…”
Section: Discussionmentioning
confidence: 85%
“…These researchers found the highest number of plant species on the baulk separating crops grown by traditional methods on small-scale farms. The high number of species on this baulks caused by low nutrient abundance (Feledyn-Szewczyk, 2007;Malecka et al, 2015), as well as the lack of interference with the communities in the form of mowing (grazing) or pesticide spraying. Most species on the baulk produce seeds generatively, and there were favourable conditions on the baulks for their maturation and seeding (Brągiel and Trąba, 2013).…”
Section: Species Compositionmentioning
confidence: 99%